2022
DOI: 10.5435/jaaosglobal-d-22-00012
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of COVID-19 on Pediatric Traumatic Orthopaedic Injuries: A Database Study

Abstract: Introduction: Stay-at-home orders and other social distancing restrictions had a profound effect on the lives of children during the pandemic. This study characterizes pediatric orthopaedic injuries and in-hospital outcomes during the COVID-19 pandemic and compares them with pre-COVID patterns. Methods: A retrospective review of pediatric patients presenting to hospitals with Pennsylvania Trauma Systems Foundation designations was performed. All patients younger than 18 years who presented with orthopaedic inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Multiple other studies have demonstrated similar trends with decreased playground-related injuries and increased bicycle-related injuries during the pandemic. 6,19 Malige et al 20 found results coinciding with previous evidence demonstrating a decrease in injuries occurring at sporting areas, parks, and pools. Even though that study did not explicitly incorporate playgrounds into their findings, it showed changing child behavior during the pandemic leading to new patterns of injury.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Multiple other studies have demonstrated similar trends with decreased playground-related injuries and increased bicycle-related injuries during the pandemic. 6,19 Malige et al 20 found results coinciding with previous evidence demonstrating a decrease in injuries occurring at sporting areas, parks, and pools. Even though that study did not explicitly incorporate playgrounds into their findings, it showed changing child behavior during the pandemic leading to new patterns of injury.…”
Section: Discussionsupporting
confidence: 66%
“…Even though that study did not explicitly incorporate playgrounds into their findings, it showed changing child behavior during the pandemic leading to new patterns of injury. 20 Further knowledge relating to the particular mechanisms of injury could help to potentially prevent injuries in the vulnerable pediatric population during future societal events.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding body region, patients sustained upper extremity (38.6%) and trunk (31.2%) injuries most commonly before the pandemic and there was no significant change in anatomic distribution of injuries during the pandemic. The pandemic also affected the location of sports-related injuries appearing to shift away from the 'sport' setting towards occurring at home and other alternative settings, a finding which has been demonstrated in prior work [9,11,[25][26][27].…”
Section: Discussionmentioning
confidence: 73%
“…Studies on pediatric populations from both high-income countries (HICs) and LMICs have reported that, in many instances, pandemic-related restrictions were associated with a reduction in certain types of injuries, such as road traffic injuries (RTIs) 15–17 or sports and leisure injuries, 15 18–22 and an increase in injuries that are more likely to occur in and around the home, such as burns 15 17 21–24 and certain types of falls from heights. 19–21 25 There are also indications of excess risk of violence-related injuries occurring at home, for example, injuries inflicted on children by either physical abuse and maltreatment 20 26–28 or sexual violence. 29–31 It is of note, however, that these differences are not consistent across studies and settings.…”
Section: Introductionmentioning
confidence: 99%
“…29–31 It is of note, however, that these differences are not consistent across studies and settings. 15 18 22 26 27 32 33 Furthermore, in addition to changes in the number and epidemiological characteristics, studies have shown an increase in injury severity during the pandemic, whether viewed by the nature of the injuries, 15 21 25 33 their severity, 16 21 22 25 the provision of intensive care unit (ICU) treatment, 20 21 25 27 or injury-related in-hospital mortality. 20 …”
Section: Introductionmentioning
confidence: 99%